PENGARUH BALIHO (COVER BUILDING) TERHADAP MINAT MAHASISWA BARU KULIAH DI POLITEKNIK LP3I JAKARTA KAMPUS SUDIRMAN TANGERANG - Sudrajat, Deny (POLITEKNIK LP3I JAKARTA, 2018)
AbstractThe purpose of the research conducted at the Polytechnic of LP3I Jakarta, Sudirman Tangerang Campus was to find out whether there was a billiard effect (cover building) made on the interest of new students to study at Politeknik LP3I Jakarta, Sudirman Campus, Tangerang. Research is associative research to determine the relationship between two variables, the approach used is the method of data analysis quantitative research using statistical methods .. Using a questionnaire instrument with respondents of the students of the Polytechnic LP3I Jakarta Campus Sudirman Tangerang. in it is a closed question of measurement using a Likert scale. In this study the sampling technique used is Non Probability Sampling, especially Purposive Sampling technique, which uses census techniques. In this research at the Polytechnic of LP3I Jakarta Sudirman Campus, the sample was determined only by the polytechnic students of LP3I Jakarta Kampus Sudirman all levels 1 (one), 20 student respondents in the academic year 2018 - 2019. From the results of data analysis, interest in the average cover building interpretation number 3.62 is included in either the criteria or cover building, according to them, interesting and visible results of the average interest in studying at Politeknik LP3I Jakarta Sudirman Campus, the average interpretation rate is 3.67, including the criteria of good or interest. to study at the Jakarta Polytechnic LP3I Sudirman Tangerang campus is high. Correlation test results obtained only 0.03 and refers to the product moment correlation table of the relationship or the influence of billboards (cover building) on the interest of new students to study at the Politeknik Lp3i Jakarta Sudirman Campus in Tangerang, the effect is very low. From the results of the determinant coefficient, the effect is only 0.09% while the remaining 99.91% of students' interest in studying at the Jakarta Polytechnic LP3I Sudirman campus in Tangerang is influenced by other factors not discussed in this study. The level of correlation and determinant is very low but the significance test shows that t count is smaller than t tabl, the t count value <t table (0, 126 <2,086). then the research hypothesis can be concluded that Ho is accepted and Ha is rejected. That is, there is no variable influence. X Bill Cover Cover for Y variables Interest in New Students Lecture at the Polytechnic of LP3I Jakarta (PLJ) Campus Sudirman in Tangerang.Keyword: Cover Building and Interesting College